Understanding Students’ Experiences of Collaborative Networked Learning - Jones, Christopher R. (Proceedings of the International Conference on Networked Learning, 2000)
This paper explores students’ experiences of collaborative learning mediated by a computer conferencing system. The paper presents initial findings from a set of interviews carried out as part of the JISC/CALT project Networked Learning in Higher Education. The paper examines students’ work on a collaborative assignment as part of a distance learning course using individual interviews. The methodological approach adopted is broadly phenomenographic (Manon 1994). In addition to interview data the author was the local tutor and observed the course in progress. The paper complements a recent research report, which provides an overview of the course and places the project assignment in the overall course setting (Kear and Heap l 999). The paper explores the relationship between course content and the process of work. It examines the assessment criteria and interpretations made of them by students. It goes on to examine the variety of interpretations that the students had and what impact it had on their assessed work. This is complemented by comparison with the work done by students working collaboratively in a place based setting (Jones and Cawood 1998). In particular the use of available technologies is explored and the ways in which students bring together the variety of communication channels that are available. It is noted how students use communications outside the conferencing system despite explicit instructions to work within the system.